AI for humanitarianism : fostering social change through emerging technologies - Ajibesin, Adeyemi Abel; Vajjhala, Narasimha, 1978- (Boca Raton, FL : CRC Press, 2025)
"This book explores the transformative potential of Artificial Intelligence (AI) in addressing critical humanitarian challenges. It examines AI's role in enhancing emergency responses, poverty alleviation, and healthcare"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Humanitarianism -- Technological innovations; Humanitarian assistance -- Technological innovations